Chiral dichroism in bi-elliptical high-order harmonic generation. (28th February 2018) - Ayuso, David; Decleva, Piero; Patchkovskii, Serguei; Smirnova, Olga
Abstract: The application of strong bi-elliptically polarized laser fields to the generation of high-order harmonics in organic molecules offers exceptional opportunities for chiral recognition and chiral discrimination. These fields are made by combining an elliptically polarized fundamental, typically in the infrared range, with its counter-rotating second harmonic. Here we present a theoretical study of the harmonic emission from the chiral molecule propylene oxide in bi-elliptical fields. Our calculations include, for the first time in such a complex system, accurate photorecomination matrix elements, evaluated using the static-exchange density functional theory method. We show that bi-elliptical light can induce strong chiral dichroism in the harmonic spectra of chiral molecules in a broad range of harmonic numbers and ellipticities.